Factors influencing survival and short-term outcomes of very low birth weight infants in a tertiary hospital in Johannesburg - Ingemyr, Kristin; Elfvin, Anders; Hentz, Elisabet; Saggers, Robin T.; Ballot, Daynia E. (Frontiers in Pediatrics, 2022)
Background The neonatal mortality rate in South Africa is lower than the global average, but still approximately five times higher than some European and Scandinavian countries. Prematurity, and its complications, is the main cause (35%) of neonatal deaths. Objective To review the maternal, delivery period and infant characteristics in relation to mortality in very low birth weight (VLBW) infants at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH). Methods This was a retrospective descriptive study of VLBW infants admitted to the neonatal unit at CMJAH. The characteristics and survival of these infants were described using univariate analysis. Results Overall survival was 66.5%. Provision of antenatal steroids, antenatal care, Caesarean section, female gender, resuscitation at birth and 5-minute Apgar more than five was related with better survival to discharge. Among respiratory diagnoses, 82.8% were diagnosed with RDS, 70.8% received surfactant therapy and 90.7% received non-invasive respiratory support after resuscitation. At discharge, 59.5% of the mothers were breastfeeding at discharge and 30.8% spent time in kangaroo mother care. Conclusion The two-thirds survival rate of VLBW infants is similar to those in other developing countries but still remains lower than developed countries. This may be improved with better antenatal care attendance, coverage of antenatal steroids, temperature control after birth, improving infection prevention and control practices, breastfeeding rates and kangaroo mother care. The survival rate was lowest amongst extremely low birth weight (ELBW) infants. Further resources allocated to this sub-group of ELBW infants would make a meaningful impact in improving neonatal survival in South Africa.